Reforming Corporate Accounting through Sustainable Finance: Insights on Green Bonds, ESG Disclosure, and Circular Economy Integration - Ibrahim, Fifi Nurafifah (Sinergi International Journal of Accounting and Taxation, 2024)
This narrative review explores the evolving integration of sustainable finance within accounting frameworks, focusing on green bonds, ESG disclosure, circular economy, and climate-related financial reporting. The study aims to understand how accounting practices are adapting to sustainability imperatives and identify critical trends, challenges, and strategies. Literature was collected from Scopus and Google Scholar using targeted keywords and Boolean operators. Peer-reviewed studies were included based on their relevance to sustainable accounting and financial governance. Findings reveal that green bonds significantly enhance corporate green innovation, while circular economy models influence cost structures and promote transparent sustainability reporting. Biodiversity accounting is emerging as a vital tool for integrating ecological risk into ESG frameworks. Moreover, financial institutions are improving climate risk disclosures through digitalization and strengthened governance. These findings challenge traditional accounting paradigms and emphasize the need for reform that incorporates long-term ecological and social impacts. The review highlights systemic barriers, such as inconsistent regulations and limited institutional capacity, and proposes digital transformation and global standardization as key solutions. It concludes that accounting must evolve to support environmental responsibility and long-term value creation. Future research should explore the financial impact of ESG investments and the scalability of digital tools in sustainability reporting.